THE IMPACTS OF FASTING PERIODS ON FOOD INTAKE, GROWTH RATE, COMPENSATORY GROWTH, AND EFFICIENCY OF FEED UTILIZATION IN BLUE TILAPIA (Oreochromis aureus) REARED IN BRACKISH WATER PONDS - Priadi Setyawan; Adam Robisalmi; Nunuk Listiyowati; Raden Roro Sri Pudji Sinarni Dewi; Imron Imron (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2012)
Blue tilapia (Oreochromis aureus) has known as euryhaline species refers to wide range of salinity tolerance. The pure population or hybrid with other strain of tilapia can be a good candidate in marginal coastal land use. Tilapia is the most important aquaculture species in Indonesia. Refers to FAO 2010, Indonesia is the third biggest of tilapia production after China and Egypt. One of the main problems in aquaculture is their feed as the major cost in fish farming. Various techniques had carried out to reduce of feed cost such as improving fish quality, sex reversal and feed management. This research aimed to determine of compensatory growth in tilapia as one technique in feed management. Fry obtained from natural spawning in freshwater pond. Acclimatization in 20 ppt made in aquarium for 4 days after one month reared in hapas. Fish reared in 2 m x 1 m hapas with five treatments and three replications. This research had conducted at brackish water pond in Yogyakarta. The treatments is A: one day fasting and six days feeding (1/6), B: 2/5, C: 3/4, D: 4/3 and E is control. Results showed that the biggest of average weight gain is treatment of E (68.36 g) followed by A (66.38 g), B (62.44 g), C (43.56 g), and D (27.30 g) respectively. One-way ANOVAs analysis with 95% of interval confidences continued with Tukey’s Pairwaise comparison showed that nothing significant different between E, A, and B. The biggest of daily growth rate and specific growth rate is E (0.75 g/day and 4.68 %bw/day) followed by A (0.73 g/day and 4.65 %bw/day); B (0.69 g/day and 4.58 %bw/day); C (0.48 g/day and 4.18% bw/day) and D (0.29 g/day and 3.65% bw/day) respectively. Survival rate of A is 73.00% followed by E. 72.00%, C. 71.00%, D. 69.69%, and B. 67.00% respectively. Feed conversion ratio of D is 0.83 followed by C (0.87), B (0.98), A (1.16), and E (1.41). Food efficiency ratio of D is 127.06% followed by C (118.75%), B (106.09%), A (88.87%), and E (73.38%). These results indicate that fasting of one day and two days has no significant effect on fish growth. Treatment A and B is the better treatment for fish culture refers to the better value of FCR, FER, and total weight gain.